Challenges and Strategies in Implementing Nature Education through a Kindergarten School-based Curriculum: A Case Study in Jiangsu, China - JIE ZHANG; Mohd Nazri Bin Abdul Rahman (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study explores the challenges and strategies of implementing nature education through school-based programs in Jiangsu Province kindergartens. Interviews with teachers from five kindergartens revealed experiences of integrating natural resources into daily teaching. Results showed that nature education, though valued for promoting holistic child development, faces challenges like insufficient theoretical guidance, weak teamwork, and inconsistent parental support. Public kindergartens benefited from community support and resource integration, while private ones struggled with systematic planning. The study recommends enhancing teacher training, reinforcing collaboration, improving curriculum assessment, increasing parental involvement, and incorporating forest education concepts to boost nature-based learning. This study provides valuable insights through a comprehensive analysis of nature education in China at the local level, and provides strong support for the improvement of nature education practice by improving the quality of early childhood education through a multidisciplinary perspective.